Episodes in Van Bibber's Life - Davis, Richard Harding, 1864-1916 (Salt Lake City, UT : Project Gutenberg, 1995)
"Episodes in Van Bibber's Life" by Richard Harding Davis is a collection of short stories written in the early 20th century. The book revolves around the character of Young Van Bibber, a charming and somewhat whimsical figure who finds himself in various humorous and poignant situations that reveal insights into human nature and society. The stories blend comedy with deeper reflections, often exploring themes of friendship, compassion, and social critique. The narrative takes readers through a series of episodes in Van Bibber$1 (Bs life, showcasing his interactions with a colorful cast of characters. In one story, he navigates the chaotic atmosphere behind the scenes of a comic opera, forging a bond with a young girl performer, revealing both the innocence of childhood and the darker undercurrents of the theatrical world. In another episode, he humorously attempts to prove his bravery and cleverness by searching for a missing dog, only to find himself in a series of amusing predicaments. Through these engaging tales, Davis paints a vivid picture of life in his time, with Van Bibber serving as a relatable and often endearing protagonist who navigates both trivial pursuits and weighty moral dilemmas. (This is an automatically generated summary.)s
Her first appearance -- Van Bibber's man-servant -- The hungry man was fed -- Love me, love my dog.
Release date is 1995-09-01
Keywords: Fiction; Short stories, American